Electrochemical Detection of Adrenaline Using Nafion–Trimethylsilyl and Nafion–Trimethylsilyl–Ru2+-Complex Modified Electrodes - R. Aguilar-Sánchez; D. A. Durán-Tlachino; S. L. Cabrera-Hilerio; J. L. Gárate-Morales (Electrochem, 2025)
The preparation and properties of Nafion–TMS (Nafion–trimethylsilyl) and Nafion–TMS–Ru2+-complex modified GC electrodes are reported for the electrochemical oxidation reaction of adrenaline (AD). The structure of Nafion–TMS was studied by atomic force microscopy. The incorporation of [Ru(bpy)3]2+ and [Ru(phen)3]2+ complexes into Nafion–TMS was investigated by UV-vis spectroscopy, providing information about the interaction of the modified Nafion–TMS–Ru2+-complex composite. According to electrochemical studies, the electrodes modified with this composite polymer showed a faster electron transfer and greatly improved kinetics for the redox reaction of AD in standard solutions when compared to bare and Nafion–TMS modified electrodes. The oxidation current increased linearly with adrenaline concentration in the range from 1 to 20 mM and 1 to 100 mM for Nafion–TMS and the modified Nafion–TMS–Ru2+ complex, respectively. A strong pH dependence on the electroanalytical parameters was found for adrenaline detection, indicating that electron transfer reaction occurs in tandem with proton transfer.